Observation of gravitational waves from a binary black hole merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (World Scientific Publishing, 2017)
Albert Einstein's general theory of relativity, first published a century ago, was described by physicist Max Born as the greatest feat of human thinking about nature.We report on two major scientific breakthroughs involving key predictions of Einstein's theory: the first direct detection of gravitational waves and the first observation of the collision and merger of a pair of black holes. This cataclysmic event, producing the gravitational-wave signal GW150914, took place in a distant galaxy more than one billion light years from the Earth. It was observed on September 14, 2015 by the two detectors of the Laser Interferometer Gravitational-Wave Observatory (LIGO), arguably the most sensitive scientific instruments ever constructed. LIGO estimated that the peak gravitational-wave power radiated during the final moments of the black hole merger was more than ten times greater than the combined light power from all the stars and galaxies in the observable Universe. This remarkable discovery marks the beginning of an exciting new era of astronomy as we open an entirely new, gravitational-wave window on the Universe.